KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBELAJARAN DI ERA DIGITAL - Iwantoro Iwantoro (JIE (Journal of Islamic Education), 2017)
In this digital era the learning process undergoes significant changes, from teacher's approach to students to the use of media in learning. Islamic Education Teachers need to improve their competence because of the stigma that teachers of Islamic Education are said to be "ancient teachers" who have difficulty following the development of information and technology world in learning. The purpose of this study is to describe the competence of teachers of Islamic Education in the digital era. Therefore, in this study, it is discussed clearly about the competence of teachers, milenia students, and learning in the digital era and its challenges, as well as the strategy of Islamic Education teachers in overcoming the challenges of learning in the digital age. The method used is the review literature of several journals and related references to illustrate how it should be a teacher in the digital age. In the context of teachers in the digital age, they should be able to use learning approaches that are based on information and communication technology so that learners are easier to follow because the information they get is very fast from cyberspace. The conclusion is that teachers of Islamic Education are highly demanded to develop their ability in using learning media based on technology and information in learning process and no longer require students to cling to textbooks only. So that the learning process more achieve the target and provide a broad space to learners to develop the creativity of learning